1978
DOI: 10.1152/ajpheart.1978.235.1.h29
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low- and high-pressure baroreceptors on plasma renin activity in humans

Abstract: We evaluated effects of the low- and high-pressure baroreceptors on plasma renin activity (immunoassay) using graded lower body suction (LBS) in six healthy men. LBS at -10 and -20 mmHg for 10 min decreased central venous pressure without changing arterial pressure and thereby presumably reduced low- but not high-pressure baroreceptor inhibition of renin release. LBS at these levels produced forearm vasoconstriction, but did not increase renin. LBS at -40 mmHg decreased central venous and arterial pulse pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…[3][4][5][6][12][13][14][15][16] These uniform findings of sympathetic activation directed to tissues governed by the baroreflexes have prompted the concept that impaired baroreflex restraint underlies sympathetic activation. It is unknown if increased sympathetic neural outflow in heart failure is limited to regions governed by the baroreflexes or is generalized to all tissues -a distinction with mechanistic implications.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…[3][4][5][6][12][13][14][15][16] These uniform findings of sympathetic activation directed to tissues governed by the baroreflexes have prompted the concept that impaired baroreflex restraint underlies sympathetic activation. It is unknown if increased sympathetic neural outflow in heart failure is limited to regions governed by the baroreflexes or is generalized to all tissues -a distinction with mechanistic implications.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Furthermore, there is evi-dence to suggest that cardiopulmonary receptors do have effects on peripheral blood flow in man (Abboud and Mark, 1979;Walker et al, 1980). With respect to this point, the previously cited studies of Mark et al (1977) and Goldsmith et al (1983) are of interest. As discussed earlier, these investigators reported that low levels of LBNP decreased central venous pressure, but had no effect on plasma renin and ADH levels, respectively, unless the stimulus caused arterial pressure to decrease.…”
Section: Discussionmentioning
confidence: 97%
“…This degree of lower body negative pressure produces a selective stimulation of cardiopulmonarv receptors (11,36). The only other report on lower body negative pressure and renin response (13) prima facie appears to speak against a role of cardiopulmonary receptors in renin regulation in man. Thus, Mark ancl Abboud (13) applied -10 and -20 mm Hg negative pressure for 10 min and did not find a reninl increase in six subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In one report on stimulation of low pressure receptors in humans, plasma renin increased (12), whereas in another report (13) such an increase was not observed. Both studies investigated small groups and used low degrees of lower body negative pressure as a means of decreasing right atrial pressure without effecting changes in arterial pressure.…”
Section: Introductionmentioning
confidence: 98%